Sarawak Sports Corporation: strategic plan 2025 - Samshuddin, Adilaila; Jumry, Ahmad; Isau, Alexander Sirai; Poni, Andrea; Amiezan, Awang; Awang Redzuan, Awang Putrayusrie; Eskandar Eyaw, Azwan; Yee, Bong Siang; Sawin, Beatrice; Resat, Budi Ariyadi; Ahmad, Dedia Sarini; Donald, Delvina; et al. (Perpustakaan Tun Abdul Razak, UiTM Cawangan Sarawak, 2025)
The Sarawak Sports Corporation (SSC) Strategic Plan serves as a comprehensive roadmap to drive the organization’s efforts in establishing Sarawak as the nation’s leading sports powerhouse.This plan aligns SSC’s vision, mission, and strategic objectives, ensuring a focused approach to sports development and management. It outlines measurable key performance indicators (KPIs) designed to track and support the attainment of SSC’s strategic goals while detailing actionable strategies to enhance the corporation’s operational efficiency and impact. By fostering collaboration, promoting excellence, and leveraging innovative practices, this strategic plan empowers SSC to build a vibrant, inclusive, and sustainable sports ecosystem that aligns with both national aspirations and Sarawak’s unique strengths.